Remote work, training initiatives, and employee well-being: insights from selected Nigeria’s manufacturing sector - Okpaegbe, IKEMSINACHI J.; Adebanji, AYENI; Christo, BISSCHOFF; Ojochide, PETER Fred; Joseph, SEKHAMPU (International Journal of Innovative Research and Scientific Studies, 2025)
This study explored the influence of diversity and inclusion, training and development, and working from home on workplace outcomes in selected manufacturing organizations in Nigeria. With a quantitative approach and regression analysis via E-Views statistical software, the study tested three hypotheses to ascertain the significance of these organizational practices on workplace culture, employee well-being, and stress management. Findings revealed that diversity and inclusion have a strong and significant positive effect on workplace culture, accounting for 52.6% of the variance of the dependent variable. Similarly, training programs had a significant effect on employee well-being but with a moderate effect, accounting for 11.9% of the variation. Remote work revealed a large effect on stress management, indicating that flexible work is critical in reducing the stress levels of employees. All the models were significant at 5%, and the Durbin-Watson values fell within the tolerable range, indicating no autocorrelation. The study concludes that inclusive policy implementation, investment in training, and remote work adoption are strategic determinants of workplace culture, employee satisfaction, and organizational performance in the Nigerian manufacturing sector. The findings have practical implications for policymakers and human resource managers committed to establishing an inclusive and productive workplace.